Optimal contracts and inflation targets revisited - Torsten Persson; Guido Enrico Tabellini (Sveriges Riksbank, 2024)
We revisit the optimal-contract approach to the design of monetary institutions, in the light of the Zero Lower Bound (ZLB) on interest rates and the resort to Quantitative Easing (QE) in recent years. Four of our lessons have not yet been incorporated in the practices of inflation targeting central banks. First, the optimal contract and the implied inflation-targeting regime should condition on being at the ZLB or out of it. Second - as already argued by others - the optimal inflation target should be raised to deal with the possibility of being at the ZLB, and more so the greater the risk of being there. But this qualitative lesson does not appear to warrant major quantitative changes of inflation targets. Third, the relevance of the ZLB suggests that it may be desirable to expand central bank mandates to encompass financial stability, broadly defined, besides price and output stability. Fourth, accountability for inflation performance is a central mechanism in a successful monetary-policy framework. How exactly to change those mechanisms in practice is a new and difficult challenge, which is at least as important as the search for optimal policy rules that has attracted so much recent attention.
Keywords: D02; E31; E58; H11; 330; Inflation targets; optimal contracts; Zero lower bound